2019
DOI: 10.1002/pssb.201800594
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Generalized Kadanoff–Baym Ansatz

Abstract: The study of electron transport is easier if the Kadanoff-Baym equations (KBE) are simplified using the Generalized Kadanoff-Baym Ansatz (GKBA). For molecular bridges, GKBA is empirically known to safely work for weak and flat tunneling functions. It fails, if either of the conditions is not satisfied. The case in point is a molecular bridge formed by an Anderson type local center treated in the mean field and linked by tunneling junctions to two ferromagnetic electrodes whose tunneling functions simulate nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For this reason, Hubbard-like models have been applied in many contexts and to a wide typology of systems, both in and out of equilibrium, see, e.g., Refs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, Hubbard-like models have been applied in many contexts and to a wide typology of systems, both in and out of equilibrium, see, e.g., Refs. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…However, these NEGF simulations are hampered by an unfavorable scaling with the simulation duration according to T 3 resulting from the two-time structure of the NEGF and the memory effects in the collision integral (see below). This behavior can be relieved by applying the Generalized Kadanoff-Baym ansatz (GKBA) [16,17] which reduces the dynamics of the NEGF, G(t, t ), to propagation along the time diagonal, t = t . It could be demonstrated that, indeed, the expected improvement of the scaling, N 3 t → N 2 t (in the following we will use the number of discretization time steps N t = T /∆t), can be achieved in practice for the selfenergy in second order Born approximation (SOA) [18,19] where initial correlation effects can be treated even more efficiently [20,21].…”
mentioning
confidence: 99%
“…Extensions to the single-level quantum devices have included the spin degree of freedom for the study of spin currents, magnetism and torque [57,[398][399][400][401][402][403], establishing that, e.g., tunneling magnetoresistance may transiently develop negative values, and the electronic interactions may enhance this effect. In this regard, the GKBA reconstruction has been shown to capture the essential features of magnetic tunnel currents [404][405][406][407].…”
Section: Electronic Transportmentioning
confidence: 99%